Humanism Versus Devilsm: Religious Identities in Brontë's Wuthering Heights - Gebreen, Hayder; Al-Eli, Mohammed. S. Jassim (RIRAI Publisher, 2025)
Wuthering Heights by Emily Brontë is a Gothic masterpiece that intricately explores love, vengeance, class, and identity within the desolate Yorkshire moors. Religion emerges as a complex force shaped by the characters' moral, social, and psychological landscapes. Using Gothic Criticism and a comparative religious approach, this study examines how Christianity, Judaism, and Islam influence the novel’s themes and conflicts. At the heart of this exploration is Heathcliff, a figure straddling humanity and Satanism. His defiance of divine authority and supernatural bond with Catherine position him as both a Gothic antihero and a theological enigma. Through characters like Heathcliff, Joseph, and Catherine, Brontë questions faith, free will, and morality, challenging Christian traditions. The study analyses religious elements in the novel, highlighting faith as both a source of comfort and control. The final chapter scrutinizes Heathcliff’s ambiguous identity through scriptural references and Gypsy traditions, assessing his human and devilish aspects. By examining Gothic elements alongside religious themes, this research reveals the profound spiritual and existential dilemmas embedded in Wuthering Heights. Ultimately, it argues that religion is not merely a backdrop but a central force shaping character identities, conflicts, and resolutions in Brontë’s dark and tumultuous narrative.